Análise teórica do jogo da Batalha dos Sexos e uma proposta experimental via Ressonância Magnética Nuclear - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
The main objective of this work is to study the game of the Battle of the Sexes in the quantum version, for two players Alice and Bob. A theoretical analysis is substantiated applying the protocol elaborated by Eisert et al., in which apply properties oficial entangled strategies. In this sense, it is possible to demonstrate that the entanglement optimized the equilibria of the game. For the case where the players choose the profile of quantum strategies operators ( ^ UA 0; 8 ; ^ UB 0; 8 ) or ( ^ UA 0; 3 8 ; ^ UB 0; 3 8 ) the dilemma can be solved. By means of the theoretical results a proposal of experimental implementation of the game in the condition of maximum entanglement is purposed by Nuclear Magnetic Resonance technique.
Theoretical analysis of the Battle of the Sexes game and an experimental proposal by Nuclear Magnetic Resonance
Keywords: Processamento de informação quântica; Teoria dos Jogos Quânticos; Ressonância Magnética Nuclear de estado líquido; Quantum information processing; Quantum game; Liquid state NMR; CNPQ::CIENCIAS EXATAS E DA TERRA::FISICA